Estudo das propriedades vibracionais do complexo de β-alaninato de níquel (II) em altas pressões - Aguiar, Luciano Vieira de (2019)
For many years amino acid crystals aroused much interest due to their application in areas such as non-linear optics. However, purely organic compounds have certain drawbacks, in particular their structural stability. For this reason, crystals formed from metal complexes have gained space in this field of study because of their superiority to purely organic or inorganic crystals. Alanine, as well as its isomeric variants, is one of the most commonly used amino acids for the formation of such complexes. In this work we study the stability of the title compound (Ni(NH2CH2CH2COO)2.2H2O) as a function of pressure using the technique of Raman spectroscopy. Such material was subjected to pressures ranging from ambient pressure to 9,0 GPa. During the compression process changes were observed in the behavior of the vibrational modes of the material which led to the belief that such compound undergoes two phase transitions around 1,3 GPa and 3,5 GPa with possible structural and conformational modifications. When compared to other related materials, the nickel β-alaninate crystal appears to exhibit greater stability due to the presence of water molecules in its structure. Given the experimental delimitations established in this work, the modifications verified in the material were reversible.